Preparation of Nano-Sized Eucalyptus Leaves Extract and its Application on Cotton as Natural Dyes and Antibacterial Agents - Ida Nuramdhani; Nurfadilah Ikhsani; Iceu Agustinisari (Tekstilec)
Nano-emulsions of Eucalyptus globulus leaves extract in 96% ethanol and 96% methanol were successfully prepared using the method of homogenization at various speeds of 13,000 rpm, 15,000 rpm and 17,000 rpm, with the addition of non-ionic surfactant to prevent agglomeration. A phytochemical analysis showed the presence of tannin, phenol and flavonoids. The size of the resulting nano-emulsions was measured using a particle size analyser (PSA) prior to the dyeing of cotton fabrics using the two-dips-two-nips method. Antibacterial tests were carried out on the extracts and dyed fabrics. The results showed that nano-sized particles (< 100 nm) were obtained from all extracts in both solvents used at all speeds. All dyed fabrics showed good levelness in a pale-brown colour with K/S values < 1 for all samples under spectrophotometric measurement. The colour fastness of the dyed fabrics to washing and rubbing were good to very good, with grey scale values ranging between 4/5–5. Antibacterial tests in Staphylococcus aureus bacterium showed that the eucalyptus leaves extract solution exhibited antibacterial ability, as evidenced by the formation of clear zones around the wells. Much better antibacterial activity was demonstrated by the dyed fabrics. Changing the particle size to nano increased the effectiveness of the antibacterial activity of the Eucalyptus globulus. Results showed that the nano-sized eucalyptus leaves extract demonstrated a more significant antibacterial activity than dyeability.